Integrasi Artificial Intelligence dalam Pembelajaran Pendidikan Agama Islam - Wahyuni, Andi Eki Dwi; Yaumi, Muhammad; Arsyad, Azhar; Husain, Saddam (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This article aims to explore the integration of artificial intelligence in Islamic Religious Education (PAI) learning to improve the effectiveness, efficiency, and inclusivity of the learning process, as well as the benefits and impacts of AI in PAI. This study uses a qualitative approach using the literature review method. This method involves collecting, analyzing, and synthesizing relevant literature, including journal articles, books, reports, and conference proceedings, to identify existing practices, challenges, and potential advancements in this field. The data is sourced from leading academic databases such as Google Scholar. The inclusion criteria prioritize research that addresses the application of AI in education, its role in improving Islamic learning, and related ethical considerations. The results of the analysis show that the integration of AI in Islamic religious education has brought significant changes in the way learning and teaching are carried out. This technology provides easy access to religious information sources, such as sacred texts, tafsir, hadith, and other important literature, which supports more inclusive and in-depth learning. AI also allows for personalized learning that suits the individual needs of learners, helping to improve understanding of religious concepts more effectively. Additionally, AI offers an edge in data analysis that allows educators to better understand learners' progress and devise more effective teaching strategies